PEMBAHARUAN DAN PROGRESIF DALAM EKSISTENSI PEMBINAAN HUKUM ISLAM SERTA PRANATA SOSIAL - Alfian, Muh (Universitas Proklamasi 45, 2020)
Islamic law has always been defined as a law that is religious and sacred, which replaces a durable law. Among the interesting questions about the adaptation of Islamic law with social developments that often occur at the base of questions concerning human beings before the sharia text. The consideration is: can Islamic law be developed by human reason or Islamic law is only taken eternally determined by God with what Islamic legal principles can be changed by social change? What developments in Islamic law can affect social change?In the course of its history, Islamic law is a dynamic and creative force, this can be seen from the instructions of the Prophet Muhammad to his friends in dealing with the sociological reality of the people at that time. But after the Prophet Muhammad died, new problems began to emerge. At the time of the ijtihad friends began to be promoted so that various interpretations emerged, the legal practice fatwa that was exemplified by the Messenger of Allah, was considered not only as a legal decision of a judge in a court of law, but also as a guide in solving problems.Society with a variety of dynamics that exist requires social change, and every social change generally requires a change in the value system and law, To oversee Islamic law remains dynamic, responsive and has a high adaptability to the demands of change, is to revive and revive the spirit berijtihad among Muslims. In this position ijtihad is an inner dynamic for the birth of change to oversee the ideals of the universality of Islam as a system of teachings that shalihun li kulli times eat. Muslims are fully aware that the source of normative-textual law is very limited in number, while new cases in the field of law are unlimited.From this explanation, it can be concluded that: firstly, Islamic law can be developed through the power of human reason, because the verse itself contains qaṭ’ī and ẓannī. Second, the tool that can be used by humans in developing Islamic law is ijtihad by using a ratio that is equipped with scientific methodological tools so that the results obtained can be justified scientifically.